The implementation of the monday–thursday fasting habituation method in strengthening the discipline character of female students at madrasah tsanawiyah tahfizh nurul iman karanganyar in the 2025/2026 academic year - Eko Supono; Muhammad Jafar Nashir (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This study examines the implementation of the Monday–Thursday fasting habituation method in strengthening the discipline character of female students at Madrasah Tsanawiyah Tahfizh Nurul Iman Karanganyar during the 2025/2026 academic year. The research employed a quantitative descriptive approach with the primary objective of analyzing the effectiveness of fasting habituation in fostering students’ disciplinary character. The research subjects consisted of 30 female students, selected through total sampling. Data were collected through observation, questionnaires, and documentation, and analyzed using descriptive statistical techniques in the form of percentages. The results indicate that 76.7% of students demonstrated a high level of disciplinary character, 16.6% were in the moderate category, while 6.7% showed a low level of discipline. Furthermore, the implementation of the fasting habituation method was categorized as very effective by 80% of respondents, while 20% perceived it as effective. The findings suggest that the consistent practice of Monday–Thursday fasting contributes positively to students’ self-control, punctuality, rule compliance, and responsibility. In conclusion, the habituation of voluntary fasting on Mondays and Thursdays plays a significant role in strengthening students’ discipline character and can be considered an effective character education strategy within Islamic secondary education institutions.